A Study on the Realization Path of "Translocality" in the Localization Strategy of Art ——Taking Yue Minjun's Promotion in the Korean Market as an Example (Journal of Global Arts Studies, 2025)
Background： In the context of globalization, how art effectively crosses cultural boundaries for successful communication, especially in the East Asian region characterized by similar cultural psychology but significant differences in aesthetic structure has become an important issue in the international communication of contemporary art. Objective： Focusing on the communication strategies of Chinese contemporary artist Yue Minjun in the Republic of Korean market, this study aims to reveal the underlying mechanism by which "localization" tactics build a "temporary affective community" to ultimately achieve a "translocal" outcome. Methods: Adopting a reconfigured E-STP cultural communication model as its core, systematically demonstrates the complete implementation path of Yue Minjun's campaign in Republic of Korea (Environmental analysis, Segmentation, Targeting, Positioning). It further explores how narrative guidance and experiential design shaped the "smile" symbol into an open "affective container." Results: Yue Minjun’s success rests not only on the recognizability of his visual iconography; more decisively, it stems from a promotional strategy that recontextualizes the “smile” motif—through narrative reconstruction and interactive-experience design—to generate an affective, translocal connection. Conclusion: This research addresses the theoretical shortcomings in current studies of localized Chinese contemporary art dissemination–namely, a lack of specific case studies and analysis of East Asian cultural market strategies. Furthermore, it offers a practical and replicable model for the international expansion of Chinese art.
Keywords: Art Localization; Translocality; Cultural Marketing; Yue Minjun